Typeface persona: a review study - Puškarević, Irma; Nedeljković, Uroš; Pintjer, Ivan (Univerzita Pardubice, 2013)
Practitioners and scholarly researchers agree that different typefaces have different personas. Document design, which is largely dependent on the use of different typefaces, stems from the content of the verbal text and the purpose of the text is expressed through typography. In an age of electronic information set in microcosmic structure, possibilities we have come to face present freedom to modify and manipulate visual attributes of a document with software packages. This practice has given the opportunity to many untrained people to become publishers and active users of type and often times this practice is directed without understanding the principles of document design and the very notion of the intended perception of type’s persona. The relevance of typeface persona is an important aspect of technical or any other document that has its intended audience. Therefore, by choosing the appropriate typeface, communicators can determine the visual tone and character of the text. This paper outlines the visual rhetoric and consequently the role of typography as a part of that rhetoric. The literature review concentrates on typeface persona in theory, practice and research, exploring the idea of ‘’atmosphere’’, connotative meaning and semantic quality of type. The paper concludes with a discussion of the demand in the field of practitioners to classify typefaces according to their persona.
Keywords: typography; visual rhetoric; typeface persona; information design